2012
DOI: 10.1371/journal.pone.0044305
|View full text |Cite
|
Sign up to set email alerts
|

miR-127 Protects Proximal Tubule Cells against Ischemia/Reperfusion: Identification of Kinesin Family Member 3B as miR-127 Target

Abstract: Ischemia/reperfusion (I/R) is at the basis of renal transplantation and acute kidney injury. Molecular mechanisms underlying proximal tubule response to I/R will allow the identification of new therapeutic targets for both clinical settings. microRNAs have emerged as crucial and tight regulators of the cellular response to insults including hypoxia. Here, we have identified several miRNAs involved in the response of the proximal tubule cell to I/R. Microarrays and RT-PCR analysis of proximal tubule cells submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 48 publications
4
48
0
Order By: Relevance
“…In addition to the classic genes that facilitate oxygen delivery, angiogenesis, and anaerobic metabolism or glycolysis, 31,33 recent studies have documented HIF-1 regulation of miRs, such as miR-210, miR-21, miR-29, and miR-127. 25,[40][41][42] This study has further shown miR-489 induction via HIF-1. Importantly, by using anti-miR-489, we have shown a protective role of miR-489 in renal tubular cells, which may contribute to HIF-1-mediated regulation of ischemic AKI and kidney injury in general.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to the classic genes that facilitate oxygen delivery, angiogenesis, and anaerobic metabolism or glycolysis, 31,33 recent studies have documented HIF-1 regulation of miRs, such as miR-210, miR-21, miR-29, and miR-127. 25,[40][41][42] This study has further shown miR-489 induction via HIF-1. Importantly, by using anti-miR-489, we have shown a protective role of miR-489 in renal tubular cells, which may contribute to HIF-1-mediated regulation of ischemic AKI and kidney injury in general.…”
Section: Discussionsupporting
confidence: 60%
“…10 MiR-127 contributed to the severity of renal I/R injury through a modulation of cell trafficking. 11 However, none of the studies presented so far evaluated the protective potential of specific pharmacologic miRNA inhibition during renal I/R injury. We provide evidence of the in vivo relevance of miR-24 in human and murine renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, a number of miRNAs, such as miR-21 [33], miR-24 [34], miR-30 family [35], miR-126 [36], miR-127 [37], miR-150 [38], miR-494 [39] and miR-687 [40], have been implicated in both protective and pathogenic roles in the development of AKI.…”
Section: Mirnas and Akimentioning
confidence: 99%
“…Microarrays and RT-PCR analysis in proximal tubule (PT) cells and in a rat renal I/R model have shown that expression of miR-127 is induced during I/R injury [37]. Subsequent analysis indicated that miR-127 could protect PT cells against I/R injury by targeting kinesin family member 3B (KIF3B) ( Figure 3C), a protein involved in cell trafficking [37].…”
Section: Mir-127mentioning
confidence: 99%
See 1 more Smart Citation